Bach2 in CD4+ T cells from SLE patients modulates B‐cell differentiation and IgG production. Issue 4 (25th February 2023) - Long, Di; Yang, Bingyi; Yang, Ming; Xiong, Feng; Zhu, Xuejing; Tan, Yixin; Wu, Haijing
Abstract: T and B cells participate in the development of systemic lupus erythematosus (SLE). BTB and CNC homology 2 (Bach2) is an irreplaceable regulator in the T and B lineages that helps to maintain immune homeostasis. However, the function of Bach2 in the pathogenesis of SLE has not been studied in depth. Flow cytometry and qRT‒PCR were used to assess Bach2 levels, bisulfite sequencing PCR was used to measure the methylation level, and silencing by electroporation and stimulation with a cytokine concentration gradient were used to investigate the effect of Bach2 on T cells. Bach2 expression was elevated in the helper T‐cell subsets (T follicular helper, Th1, Th2, Th17, and Treg cells) of SLE patients and negatively correlated with disease severity and autoantibody levels. CD4 + T cells from SLE patients had decreased methylation levels in the Bach2 promoter region. Silencing Bach2 in CD4 + T cells induced increases in the CD19 + B‐cell count, plasmablasts, and secretion of IgG by prompting the secretion of cytokines. The activation signals CD3/CD28, IL‐6, and IL‐21 upregulated Bach2 expression in CD4 + T cells. The regulation of Bach2 by cytokines and T‐cell activation signals in CD4 + T cells was shown to act on B cells and play a protective role against SLE. Abstract : Bach2 was increased in Th subsets from SLE patients and negatively correlated with systemic lupus erythematosus disease activity index. Knockdown of Bach2 in CD4 + T cells induced secretion of cytokines and IgG from B cell. Bach2 in CD4 + T cells regulated by cytokines and T‐cell activation signals.